Bagaimana Bekas Tuberkulosis Dapat Menginduksi Kanker Paru? - Elvando Tunggul Mauliate Simatupang; Arya Marganda Simanjuntak; Indra Yovi; Rohani Lasmaria Simbolon; Sri Melati Munir; Dewi Wijaya (Majalah Kedokteran Indonesia, 2023)
In 2022, there will be 10.6 million cases of tuberculosis, which is a serious problem worldwide. Thailand's cohort research after the COVID-19 pandemic found a 7-fold risk of tuberculosis infection in COVID-19 patients, pointing to a probable rise in TB cases. In order to completely eradicate TB, care must be given to patients both before and after infection, guaranteeing public health against TB infection.1,2